Investigations in storage at World Water Week - Ebrahim, Girma; Bhatpuria, Dhyey; Rex, William; Lautze, Jonathan F. (CGIAR System Organization, 2023)
The Shashe catchment of the Limpopo Basin in Botswana and Zimbabwe is a dry place: the Shashe River flows for just a few days a year, and 10 recently built dams are usually the only visible signs of water. But in the complex world of water storage, not everything is visible.